Depleted Long Noncoding RNA GAS5 Relieves Intervertebral Disc Degeneration via microRNA-17-3p/Ang-2. (15th March 2022) - Yu, Xiaojun; Liu, Qikun; Wang, Yinguang; Bao, Yuan; Jiang, Yongqiao; Li, Mengwei; Li, Zhiwei; Wang, Baodong; Yu, Lei; Wang, Shanxi; Shao, Ming; Kang, Hao
Abstract : Intervertebral disc degeneration (IVDD) remains a clinical challenge and requires more effective therapeutic targets. Long noncoding RNAs (lncRNAs) have emerged as critical modulators of multiple biological processes, such as cell proliferation and extracellular matrix (ECM) remodeling. Accordingly, the current study sets out to explore the influence of the lncRNA growth arrest-specific 5 (GAS5) on IVDD and investigate the possible involvement of microRNA-17-3p (miR-17-3p)/Angiopoietin-2 (Ang-2) axis. Firstly, the expression patterns of GAS5, miR-17-3p, and Ang-2 were characterized by RNA quantification from the isolated human degenerative nucleus pulposus (NP) tissues. miR-17-3p was found to express at an abnormal low level while GAS5 and Ang-2 expressed at aberrant high level in the human degenerative NP tissues. Utilizing dual-luciferase reporter, RNA immunoprecipitation, and pull-down assays, GAS5 was found to competitively bound to miR-17-3p and further upregulate the expression of Ang-2, a target gene of miR-17-3p. Employing gain- and loss-of-function approaches, their expressions were altered in human degenerative nucleus pulposus cells (NPCs), followed by IL-1 β treatment, in order to identify their roles in NP cell proliferation, apoptosis, and ECM metabolism. Silencing of GAS5 expression restrained the levels of cleaved caspase-3, cleaved caspase-7, cleaved caspase-9, MMP3, MMP13, ADAMTS4, and ADAMTS5 and increased collagen II and aggrecan levels. In vitro experiments also revealed that GAS5 depletion inhibited apoptosis and ECM degradation in HDNPCs, while elevating the proliferation through downregulation of Ang-2 by increasing miR-17-3p. Furthermore, in vivo data further validated that either GAS5 silencing or miR-17-3p reexpression alleviated IVDD degree with the help of IVDD mouse models. Altogether, our findings substantiated that downregulation of GAS5 reduced NPC apoptosis and promoted ECM remodeling, ultimately ameliorating the IVDD via miR-17-3p-dependent inhibition of Ang-2. We hope our discoveries offer a fresh molecular insight that can aid the development of novel therapies against IVDD.